Chemoselective hydrogenation of α, β-unsaturated aldehydes over Rh nanoclusters confined in a metal–organic framework. Issue 22 (1st June 2020) - Liu, Qinglin; Li, Yinle; Fan, Yanan; Su, Cheng-Yong; Li, Guangqin
Abstract : Rh nanoclusters confined in metal–organic framework MIL-101 have been synthesized by double solvents method, exhibiting impressive catalytic activities and high selectivity towards chemoselective hydrogenation of α, β-unsaturated aldehyde. Abstract : Selective hydrogenation of α, β-unsaturated aldehydes to achieve high selectivity towards a desirable product is still a great challenge mainly because of the complex conjugate system. Herein, Rh nanoclusters encapsulated in MIL-101 (Cr), synthesized by the double solvent method, are able to selectively hydrogenate CC of cinnamaldehyde, an α, β-unsaturated aldehyde and achieve over 98% selectivity with a conversion of 98% to a saturated aldehyde under mild conditions. Fourier transform infrared spectroscopy confirms that MIL-101 acts as an aldehyde protector to suppress the reactivity of CO, and the X-ray photoelectron spectroscopy (XPS) data indicate that the electropositive Rh, owing to the electron transfer from Rh to MIL-101, preferentially absorbs CC rather than CO leading to improvement of the selectivity towards saturated aldehydes. In addition, Rh@MIL-101 can also efficiently catalyse hydrodefluorination of aryl fluorides with good stability. This work provides a basic strategy to develop other selective heterogeneous catalysts via structural modulation for synergetic catalysis.